Measuring Environmental Performance for Automobile Industry - Research Work - Vedak, Amol (2009)
At present the companies across the world are pressurised by the Governments to control their environmental impact – Carbon reduction, waste disposal, water utilization, recycling etc. Many governments such as UK, Japan, and Australia have signed Kyoto agreement and have accepted challenging targets. To ensure that the companies follow the targets governments are not only tightening the regulations but also incentivising the industries towards carbon reduction. Also various reports suggest that the consumers in developed countries are becoming socially responsible. They understand the importance of purchasing the goods from environmentally responsible company. The changes in government regulation and consumer’s taste have impacted many industries significantly. Automobile sector is one of the most impacted sectors due to these changes in the external environment. To guide organisational environmental agenda, many researchers have developed various frameworks. However, these tools are generic and provide scattered set of tools for calculating GHG emission and other impacts such as waste, energy, water etc. Also, these tools are not industry specific. Although, the companies in automobile industry have taken steps towards reducing their environmental impact and publishing it in their annual reports, at present they are not supported by comprehensive framework and tools to manage their efforts. This report attempts to provide a solution to this need. To come up with set of suggestions and to advice sector specific tools, the report takes systematic approach towards resolution of the problem. To begin with, the report provides a literature review on the research topic. Moving ahead, it tries to understand why metrics is important for company’s strategic progress and how it can be helpful. The report also analyses some of the environmental matrices developed by various researchers. Further it dwells specific into Indian automobile industry to analyse how Indian government regulations have impacted the entire industry. The report also analyses some of the important companies in Indian automobile industry (Tata, Maruti, Hero Honda, BMW India etc). and their environmental initiatives. With one hand on the academia and the other on industry needs, the report attempts to develop a GHG Protocol based solution that can be utilised by the automobile industry. Word Count: 8310